Memantine for Multiple Sclerosis: A Systematic Review and Meta-Analysis of Randomized Trials - Turalde, Christian Wilson R.; Espiritu, Adrian I.; Anlacan, Veeda Michelle M. (Frontiers in Neurology, 2021)
Background Multiple sclerosis (MS), a disabling demyelinating disease of the central nervous system, is associated with cognitive impairment, spasticity, and fatigue. There are still no established guidelines on the management of MS-related sequela. Memantine has a potential role in reducing glutamate toxicity thereby reducing subsequent cognitive impairment, spasticity, and fatigue. Objectives This study aims to determine the efficacy and safety of memantine in preventing cognitive impairment, reducing spasticity, reducing fatigue, and controlling disability in patients with MS through review of relevant randomized trials. Methods MEDLINE, CENTRAL, Scopus, Embase, LILACS, ClinicalTrials.gov, and HERDIN were searched from inception to May 2020 for relevant trials. Results The search yielded 203 articles; four studies were included in the analysis. Pooled evidence shows that memantine compared to placebo does not significantly improve PASAT, ASS, MFIS, and EDSS scores of patients with MS. Patients who received memantine had significantly higher rates of mild adverse drug events such as dizziness, fatigue, and anxiety. Conclusion There is not enough evidence to support the efficacy of memantine in preventing cognitive decline, controlling spasticity, reducing fatigue, and preventing disability. Further researches should consider the different MS subtypes, effect of co-administration of disease-modifying therapies, longer duration of administration, and more sensitive outcome measures are needed to evaluate the potential benefit of memantine in MS.